Mewujudkan Industri Tempe Malang Ramah Lingkungan melalui Pemanfaatan Limbah Produksi sebagai Pupuk - Izza, Jasmine Nurul; Anggarani, Dinar Arsy; Aruna, Alby; Susanto, Hendra (Penerbit Goodwood, 2024)
Purpose: The implementation of this dedication activity aims to study and present various issues about the management of waste industry waste, the potential use of this waste as organic fertilizer, and actions to make Kampung Industri Tempe Sanan an environmentally friendly area. Methodology: This activity uses ABCD (Asset-based Community Development) Method. The fermentation and compositing methods used in this study were done with the preparation of a compressor tube, a compound activator such as EM4, and waste of tempe. Results: Waste composting not only minimizes the impact of waste but also produces nutrient-rich fertilizer, which is fundamental to plant growth. Local communities are actively involved, practicing participatory approaches in the collection, processing, and utilization of fertilizers, helping to raise their ecological awareness and economic capacity. The implementation of these initiatives is a real proof of the harmonious blend of industry, environment, and community. Environmental and socio-economic well-being increased, marking the successful transition of Village Industries to a sustainable and environmentally friendly model. People not only understand the value of the environment but also develop new skills that contribute to local economic development. Limitation and Contribution: This activity is limited to process soybean husk waste and only up to the manufacturing stage. This occasion impacts to Kampung Sanan’s household production waste processing. Kampung Sanan is not only a concrete example of effective waste management but also a symbol of community integration and cooperation in creating a greener, healthier, and more productive environment. It reflects the tremendous potential of multisectoral collaboration in achieving environmental and economic sustainability.